Analisis Penerapan Chatbot untuk Meningkatkan Layanan Pelanggan pada E-Commerce - Ade Wisandra; Ahmad Junaidi (Journal of Student Development Information System (JoSDIS), 2026)
The development of information technology has opened up opportunities for small and medium-sized businesses, including culinary businesses such as online cake shops, to improve the quality of service to customers. One innovation that can be utilized is the application of artificial intelligence-based chatbots to assist in the process of interacting with customers. This study aims to analyze the effectiveness of chatbot implementation in improving customer service in e-commerce cake businesses, particularly in terms of response speed to product inquiries, ease of ordering, and customer satisfaction levels. The research methods used are qualitative and quantitative methods with data collection techniques through observation, interviews with cake shop owners, and distribution of questionnaires to customers. The data obtained was analyzed using descriptive methods and statistical tests to measure customer satisfaction levels before and after the implementation of chatbots. The results showed that the implementation of chatbots could improve service efficiency with an average response time of 5 seconds for questions about cake menus, prices, stock availability, and how to order, compared to 20-30 minutes for manual services. Customer satisfaction levels increased by 38%, and the chatbot was able to handle routine questions such as product catalogs, flavor variants, prices, and delivery time estimates with 82% accuracy. This allows shop owners to focus on cake production and handling custom orders.